2019
DOI: 10.1007/978-3-030-04849-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Business and Information Technology Alignment Measurement - A Recent Literature Review

Abstract: Since technology has been involved in the business context, Business and Information Technology Alignment (BITA) has been one of the main concerns of IT and Business executives and directors due to its importance to overall company performance, especially today in the age of digital transformation. Several models and frameworks have been developed for BITA implementation and for measuring their level of success, each one with a different approach to this desired state. The BITA measurement is one of the main d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Various BITA measurement models have sprung up in different forms since then. For example, Muñoz and Avila reviewed the extant BITA measurement models and methods [39]. McAdam explained the performance measurement of BITA through a dynamic capability perspective [40].…”
Section: Theoretical Background 21 Bita Measurementmentioning
confidence: 99%
“…Various BITA measurement models have sprung up in different forms since then. For example, Muñoz and Avila reviewed the extant BITA measurement models and methods [39]. McAdam explained the performance measurement of BITA through a dynamic capability perspective [40].…”
Section: Theoretical Background 21 Bita Measurementmentioning
confidence: 99%
“…In this section we present main findings and gaps into the state of the art about BITA measurement, published in [4]. Also are presented selected relevant works about BITA focused on the customer experience, what is a key pillar for the develop of the model presented in this article.…”
Section: State Of the Artmentioning
confidence: 99%
“…A literature review [4], looking for contributions in BITA measurement at the three beforementioned alignment levels, shown that the wide research work is focused on the measurement of the internal alignment level with great advances and many approaches. This analysis showed as well that there is an absence of measurement models for the alignment with the external environment and future evolutions.…”
Section: Introductionmentioning
confidence: 99%